The Influence of Auditor Opinion, Key Audit Matters, and Company Performance on Investor Considerations in Investment Decision-Making for Companies Listed on the Indonesia Stock Exchange - Baktiar Sofian Tambunan (Journal Research of Social Science, Economics, and Management, 2024)
The study aims to determine the impact of auditor opinions, key audit matters,and company performance on investment decisions, motivated by the need for auditedfinancial statements for investors. Auditor opinion reflects whether the financial statementsare prepared in all material aspects according to applicable financial reporting standards, andwhether the auditor has obtained reasonable assurance that they are free from materialmisstatement. Key Audit Matters are those considered most significant by the auditor in thecurrent audit period. Financial performance indicators to determine whether a company'soperations over a specific period have incurred a loss, one can refer to the income statement.Profitability is the net result of a series of policies and decisions. A high level of profitabilitywhich investors use to assess company growth. The research employs a quantitative approachwith literature review and questionnaires for data collection, using purposive sampling ofinvestors in companies listed on the Indonesia Stock Exchange (IDX). The hypothesis is testedusing Multiple Linear Regression Analysis at a 5% significance level.